Views on the UAE–Belém work programme - CGIAR Climate Security Observatory (2024)
The Convention on the Protection and Use of Transboundary Watercourses and International Lakes (Water Convention), the Food and Agriculture Organization of the United Nations (FAO), International Labour Organization (ILO), International Organization for Migration (IOM), Office of the United Nations High Commissioner for Human Rights (OHCHR), Office of the United Nations High Commissioner for Refugees (UNHCR), Sanitation and Water for All (SWA), United Nations Children’s Fund (UNICEF), United Nations Development Programme (UNDP), United Nations Educational, Scientific and Cultural Organization (UNESCO), United Nations Foundation, United Nations Office for the Coordination of Humanitarian Affairs (OCHA), United Nations University - Institute for Environment and Human Security (UNU-EHS), World Food Programme (WFP) and the World Health Organization (WHO) are pleased to submit collective inputs on the two-year UAE–Belém work programme on indicators for measuring progress achieved towards the targets in the UAE Framework for Global Climate Resilience, as invited in Decision 2/CMA.5 of the UAE Consensus.